PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ela Widasari; Mega Furwanti (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
This research was conducted with the aim of knowing that the Financial Performance and Company Size can affect the Firm Value of the LQ45 Companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The method used in this research is quantitative research methods. The population used is all LQ45 companies listed on the Indonesia Stock Exchange (BEI) using purposive sampling method. Data collection obtained through secondary data. The data analysis technique used in this research is the Classical Assumption Test which consists of (Normality Test, Heteroscedasticity Test, Multicollinearity Test and Autocoleration Test), Multiple Linear Regression Analysis Test, Correlation Analysis Test, Determination Coefficient Test, and Hypothesis Test which consists of ( Statistical t test and statistical test F).The result of t statistical test shows that the Financial Performance as X1 has a value of